The Correlation Between Work Environment And Employee's Job Satisfaction Among Generation Z - Syahida, Sarah Nuri; Ginting, Henndy (Journal of Business and Management, 2019)
Work Environment is one of the variables that impact to job satisfaction. Working conditions clearly have represented a component of job satisfaction (Sundstrom,1986). The work environment is where work is done, this can be seen as a combination of physical, virtual and social environments (Roth, Niemi, Lindholm and Loma, 2010).The appropriate work environment can fulfill employee job satisfaction will also depend on the type of employee itself. One of the type of employee is based on generation. The newest generation workers now is Generation Z. Generation Z working in Indonesia is 16,140,025 peoples and this shows great assets in the workforce. This research will examine the correlation of work environment with generation Z employee’s job satisfaction. Based on the test result, the author found that generation Z employee job satisfaction level distributed from low to high. All of variable of current work environment in this research have positive correlation with job satisfaction with all the result of significant score are more than 0.005 and the variable that have more dominant impact to job satisfaction is virtual work environment with score of pearson correlation 0.581.Keyword: physical work environment, social work environment, virtual work environment, employee job satisfaction, generation Z